Effect of pre-main-post diesel injection strategy on greenhouse gas and nitrogen oxide emissions of natural gas/diesel dual-fuel engine at high load conditions. (15th October 2021) - Yousefi, Amin; Guo, Hongsheng; Dev, Shouvik; Liko, Brian; Lafrance, Simon
Highlights: Effect of pre-main- post injection on NDDF engine was investigated at high load. Pre injection timing gives more controllability of CA50 than main and post injection. Pre-main-post injection can increase ITE by 0.37% compared to single injection. Pre-main-post injection reduces unburned methane, GHG and NOx by 13.4%, 1.5%, and 42%. Abstract: Natural gas/diesel dual-fuel (NDDF) engine technology is an interesting concept for decreasing greenhouse gas (GHG) emissions of heavy-duty diesel engines. One of the main limitations of this concept is the emissions of unburned methane which is estimated to have a GHG potential factor of 25 – 34 over a 100-year period. Our previous study has shown that a NDDF engine using pre-main-post diesel injection strategy can reduce unburned methane emissions, but yields lower indicated thermal efficiency (ITE) and higher carbon dioxide (CO2 ) and nitrogen oxides (NOx ) emissions compared to that using single diesel injection strategy under high engine load conditions due to the advanced combustion phasing. In this study, the combustion phasing of pre-main-post diesel injection strategy is further optimized with the goal to improve the ITE and reduce the GHG and NOx emissions without compromising the unburned methane emissions when compared to single injection strategy. The results reveal that changing pre diesel injection timing gives more controllability of the combustion phasing than changing the main and post diesel injection timing. A more homogenous premixed mixture of pre injected diesel – natural gas – air retards the combustion phasing which allowed further improvement of the ITE and GHG emissions of NDDF engines while maintaining the low unburned methane emissions feature of the pre-main-post injection strategy. It is found that the optimized pre-main-post diesel injection strategy is able to reduce unburned methane, GHG, and NOx emissions by 13.4%, 1.5%, and 42%, respectively, and increase ITE by 0.37% compared to single injection strategy.